What Indigenous Literatures Have to Do with Decolonization: Selections from Marilyn Dumont’s A Really Good Brown Girl (1996) and The Pemmican Eaters (2015) - Ezenwa, Chinelo (Alternative francophone, 2023)
This article explores selected poems from Dumont’s A Really Good Brown Girl and The Pemmican Eaters as critical works that address dual aspects of Indigenous decolonization struggles. While the poems from A Really Good Brown Girl adopt the language/poetics of resistance to critique cultural and linguistic discrimination, The Pemmican Eaters focuses on reclaiming and regenerating the author’s Indigenous identity. One of the strategies common to the poems is the repositioning of former derogatory terms to reclaim the Indigenous affirming meanings and histories of these words. By representing these words and memories through a Cree Métis perspective, Dumont subverts popular colonial myths and shows the truth about settler-colonization to the colonizer. Dumont’s poems offer a strong and direct critique of settler-colonization as well as the colonizer’s attempts to control Indigenous bodies and worldviews. And by so doing, they demonstrate the connections between literary activism and ongoing Indigenous journeys to sovereignty.